2017
DOI: 10.1016/j.ijmultiphaseflow.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of phase-detective intrusive probes in high-velocity air–water flows

Abstract: A comparative analysis of a wide range of air-water flow properties was conducted for two types of phase-detection intrusive probes including fiber-optical and conductivity probes. Experiments were conducted on a stepped spillway model for a skimming flow discharge q = 0.478 m 2 /s and for Re = 4.7 10 5 in a flow region just downstream of the inception point of free-surface aeration and in the fully developed flow region. The comparison of a large number of key air-water flow properties showed a very close agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…There are different proposals for energy dissipation mechanisms in open channel flows, depending on the regime analyzed. Turbulence and bubble effects play an important role in self-aerated open channels and stilling basins [13][14][15][16][17], but supercritical flows in spillways are highly influenced by roughness at the boundary [18]. The objective of the work presented in this article is to quantify the influence of aeration on the roughness boundary in high velocity and turbulent flows through friction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…There are different proposals for energy dissipation mechanisms in open channel flows, depending on the regime analyzed. Turbulence and bubble effects play an important role in self-aerated open channels and stilling basins [13][14][15][16][17], but supercritical flows in spillways are highly influenced by roughness at the boundary [18]. The objective of the work presented in this article is to quantify the influence of aeration on the roughness boundary in high velocity and turbulent flows through friction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…When air concentrations amount to over a few percent, the preferred instrumentation should be phase detection probes [96,97]. Special care must be taken in regions with near null velocities and important cross velocities, which lead to oblique impact of bubbles with the probes' tips or bubbles undetected by at least one tip (impacting the cross-correlation performance).…”
Section: Discussion On Experimental Uncertaintiesmentioning
confidence: 99%
“…A convergence analysis of the stepped spillway data showed that sampling durations T > 45 s could further improve the measurement accuracy (Appendix A). The raw voltage signals were recorded with the same LabVIEW-based data acquisition system using a high-speed acquisition unit (National Instruments USB-6366) and further details on the overall probe designs can be found in Felder and Pfister (2017) and Felder et al (2019). Table 3: Experimental flow condition and dual-tip phase-detection probe specifications for the re-analysed datasets; CP: phase-detection conductivity probe; FO: phase-detection fiber optical probe; Reynolds number Re = q/ν, with ν the kinematic viscosity of water and q the specific discharge; f : sampling rate, T : sampling duration; ∆ x: streamwise tip separation distance.…”
Section: General Remarksmentioning
confidence: 99%
“…In the present study, experimental data at step edge 101 were re-analysed. Further details on the flume and the flow conditions can be found in Felder and Pfister (2017).…”
Section: Stepped Spillway (Epfl)mentioning
confidence: 99%